Correlation between workplace stressogenic factors and sociodemographic characteristics of employees in primary and secondary health care in Doboj region - Dragana Božić (Биомедицинска истраживања, 2018)
Introduction: This paper is concerned with a comparative analysis of sociodemographic characteristics of the employees and workplace stressogenic factors in both primary and secondary health care. The assessment of the connection of stress factors, as well as subjective feelings of health workers, to their workplace was carried out. Methods: The study included 300 respondents, out of which 42.33% worked in primary and 57.67% in secondary health care. The data were collected from May to June 2016 by means of the survey conducted in the health care institutions in Doboj region. Results: The comparison of employees in primary and secundary health care, respectively, showed that there was no statistically significant difference in gender, age and total work experience in the health care institutions, while the differences in levels of education (p=0.044); the sector in which the working status is based (p<0.000); total work experience (p=0.002) and job positions (p=0.020) were statistically significant. The analysis of answers provided by the respondents showed a statistically significant difference in the distribution of respondents working in primary and secondary health care according to the answers to 76% of questions related to workplace stressors, 86% of questions related to the impact of workplace on the health status, and 40% of questions related to workplace position issues. The correlational analysis between sociodemographic characteristics of respondents and their answers concerning workplace stressogenic factors demonstrated that the employment sector (public/private sector jobs) correlated highly with the majority of stressogenic factors, followed by total work experience, total work experience in the current health care institution, age and marital status. There was the highest correlation between employment sector, as well as work experience, and the answers to the questions concerning the effect of workplace on the health status. Conclusion: Workplace stressors have varying intensity and influence on the employees in primary and secondary health care. Secondary health care respondents experience a higher degree of stress and estimate that the job has a greater negative impact on their health in comparison with primary health care respondents.
Keywords: workplace stress; sociodemographic characteristics; primary health care; secondary health care